Balloon aortic valvuloplasty in the transcatheter aortic valve implantation era : a single-center registry - Francisco, Ana Rita G. (2018)
© 2017 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.